Effect of Ginkgolide B on Non-Alcoholic Fatty Liver Disease based on Notch Signaling Pathway - Hong YU; Junzi WU; Bo SONG; Jun LI (康复学报)
Objective:To explore the interventional effect of Ginkgolide B on non-alcoholic fatty liver disease (NAFLD) based on the Notch signal pathway, and provide basis for Ginkgolide B in treating NAFLD.Methods:A total of 72 SD rats were divided into the normal group and the experiment group according to the random number method, with 12 cases in the normal group and 60 cases in the experiment group. The normal group were fed with normal fodder for 12 weeks, and the experiment group were fed with high-fat and high-sugar fodder (83.25%basic feed, 10%lard, 5%sucrose, 1.5%cholesterol and 0.25%sodium cholate) for 12 weeks to construct NAFLD animal model (The success criterion for modeling is that: there are a large number of fat vacuoles in the liver). After successful modeling, the experiment group were randomly divided into the model group, the simvastatin group, the ginkgolide B low, medium and high dose group, with 10 cases in each group. The normal group and the model group were given 1 mL/d normal saline by gavage; the simvastatin group was given 2 mg/(kg·d) simvastatin by gavage; the low, medium and high doses group were given 98%ginkgolide B by gavage at doses of 0.5, 1.0, 2.0 mg/(kg·d) respectively. After intervention for four weeks, some indexs such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) were compared; the differences of transforming growth factor-β1(TGF-β1) and tumor necrosis factor-α(TNF-α) in liver and plasma were compared; HE staining method was used to observe liver histopathological changes; Real-time fluorescent quantitative PCR method and Western blot method were used to detect the protein and mRNA expression of Notch-3, Hes-1. Results: ①The results of biochemical indicators: compared with the normal group, AST, ALT, LDL-C, HDL-C, TGF-β1 and TNF-α in the model group increased significantly (P< 0.05); compared with the model group, AST, ALT, LDL-C, TGF-β1, TNF-α of the simvastatin group, low-dose, middle-dose and high-dose group decreased significantly (P< 0.05), while there was no significant difference in HDL-C(P> 0.05); compared with the simvastatin group, there were no significant difference in AST, ALT, LDL-C, HDL-C of the low, medium and high dose group (P> 0.05), while TGF-β1 and TNF-α of the low, medium and high dose group decreased significantly (P< 0.05). ②Histopathological results: there were almost no fat vacuoles in the normal group, while a large number of fat vacuoles appeared in the model group. Compared with the model group, the number of fat vacuoles in the simvastatin group, high, medium, and low dose group decreased significantly (P< 0.05). ③The protein and mRNA expression of Notch-3 and Hes-1: compared with the normal group, the protein and mRNA expression of Notch-3 and Hes-1 in the model group increased significantly (P< 0.05); compared with the model group, the protein and mRNA expression of Notch-3, Hes-1 in the simvastatin group, low and medium high-dose group decreased significantly (P< 0.05); compared with the simvastatin group, the protein and mRNA expression of Notch-3, Hes-1 of the medium and high-dose group decreased significantly (P< 0.05).Conclusion:Ginkgolide B can improve the liver function, reduce blood lipids, and reduce inflammation of NAFLD rats. Its mechanism may be that Ginkgolide B could regulate the Notch signaling pathway by inhibiting Notch-3, Hes-1 protein and mRNA expression in liver tissue.